Constraints Perceived by Farmers in Adoption of Direct Seeded Rice Cultivation in Haryana - Anil Kumar Rohila, B.S. Ghanghas, Ajay Kumar and P.S. Shehrawat (Indian Journal of Extension Education, 2018)
The study focused on constraints perceived by farmers’ in adoption of Direct Seeded Rice CultivationTechnology in Haryana since it is being a most feasible and sustainable alternative rice-ecosystem in view ofdepleting water resources, reduced labour use and climate risks being major concerns in conventional methodof cultivation. Among constraints non- availability of quality seeds, fertilizers, weedicides and pesticides inrequired quantity and at proper time, high weed infestation in DSR in comparison to transplanting, widefluctuation in prices of basmati paddy due to lack of MSP, lack of storage facilities in villages, lack of properknowledge of irrigation schedule, non-availability of extension personnel, non-availability of agriculturalmagazines and literature in time in villages, lack of stable procurement policy for basmati rice and lack oftrained field staff to provide technical guidance during cultivation process were serious constraints faced byfarmers in adoption of DSR technology in Haryana. Concerted efforts should be made by government andnon-government agencies to address the problems faced by farmers in adoption of DSR especially qualityinputs and strengthening the capacity building of both field functionaries and farmers regarding DSR technologyfor its establishment in farmers’ field.